ANALISIS SEMIOTIKA KOMUNIKASI PERSUASIF RAJA MATARAM PADA FILM SULTAN AGUNG - Abidi, Rohmat; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
Film is a new means used to disseminate entertainment that has become a long-standing habit, as well as presenting stories, events, music, drama, comedy and other technical presentations to the general public. The important things in a film are the images and sounds, the spoken words (plus other sounds that simultaneously accompany the images), and the film music. The film Sultan Agung Thrones, Struggle and Love, is a colossal drama made by director Hanung Bramantyo in 2018. Research on this film examines persuasive communication using Roland Barthes' semiotic lens in every scene in the film to find meaning and what persuasiveness is like. contained in every dialogue scene in this colossal drama. The research carried out to examine the film Sultan Agung was by using data documentation methods and direct film observations, using qualitative methods. The technique used in collecting data is using direct observation of films to obtain information and materials for the purposes of the research. The results of this research show that persuasive communication using Roland Barthes' semiotic lens in the Sultan Agung film scene contains persuasive dialogue and there are supporting signs in facial expressions and intonation that direct the persuasive communication carried out by Sultan Agung in this scene, which is successful in making the changes desired by the communicant himself. . In general, it was found that persuasive communication as a king was always followed by his subordinates, making this persuasive communication stronger and able to change the behavior of the people around him without exception. Based on strong theory and existing journals, we know more about the figure of a great leader who, when conducting dialogue, has enormous potential in changing the behavior of the people he is talking about